Neonatal lupus erythematosus: A narrative review - Marques, Ana Raquel (2022)
Introduction: Neonatal lupus erythematosus (NLE) is characterized by the transplacental passage of maternal antibodies, mainly anti-Sjogren’s syndrome A/Ro (anti-SSA/Ro) and anti-Sjogren’s syndrome B/La (anti-SSB/La), which bind to the developing fetal tissues. Seropositive mothers may have a diagnosed disease, such as Sjögren’s syndrome, systemic lupus erythematosus, or undifferentiated connective tissue disease, but in 25─60% of cases, they are asymptomatic at the time of childbirth. Objectives: This article aimed to provide a narrative review of the current state of knowledge on NLE. Development: The clinical spectrum of NLE includes both reversible and irreversible features. Reversible clinical features, like cutaneous lesions, hematological and pulmonary abnormalities, and hepatobiliary dysfunction, disappear spontaneously as autoantibody levels decrease in the bloodstream. The most commonly reported NLE manifestation is cardiac disease. Injury to the cardiac conduction tissue may lead to defects, such as congenital atrioventricular (AV) block, which is the most severe and, in some cases, lethal NLE manifestation. NLE may also have an impact on the myocardium and endocardium, with maternal antibodies being responsible for endocardial fibroelastosis. Immune-mediated AV block may benefit from in-utero treatment with steroids. Hydroxychloroquine may also be prescribed to women with immune-mediated disorders in the preconception period. Conclusions: The management of infants affected with NLE should be performed in a tertiary care center. Postnatal pacemaker insertion may be indicated in the presence of irreversible AV block or heart failure. Erythrocyte or platelet transfusions, corticosteroids, or intravenous immunoglobulin may be indicated to treat severe disease manifestations.